The Effectiveness of Technique Positive Reinforcement in Reducing Academic Procrastination Among Final-Year Students: An Experimental Study - Linda Dwi Sholikhah; Hera Heru Sri Suryanti (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The majority of students graduate beyond the specified time limit. The research aims to test the effectiveness of positive reinforcement techniques to reduce academic procrastination among final-year students in the 9th semester of the BK study program. The results of the procrastination survey showed that the majority of students fell into the high category: 51 Students. The sampling method is purposive random sampling. Sample of 22 students. Research with an experimental process. The research design is a one-group pre-test post-test design. Intervention consists of 5 meetings, each lasting 50 minutes. The stages of the intervention are: opening, transition, core, and closing. The instruments are interviews, observations, and questionnaires. Average Pre-test: 195.68, high category. Average post-test score: 136.90, categorized as low. A decrease of 1293 (17.54%). Wilcoxon Signed Ranks Test analysis: Asymp sig (2-tailed) value = 0.000; thus, Ha is accepted. The positive reinforcement technique can significantly reduce academic procrastination among students. The practical implication of the research is to help students manage their time to complete their theses. Research implication: Students can reduce academic procrastination. Keywords: positive reinforcement, academic procrastination, students